El marxismo y la lucha contra las adicciones en la clase obrera La cuestión del alcohol en la internacional socialista y en la revolución rusa - Mignon, Carlos (Ariadna Ediciones, 2023)
This study on the debates on the question of alcohol in the socialist parties belonging to the Second International (1889-1914) and in the first years of the Russian Revolution aims to show how socialist organizations tried to address the fight against addictions in the heart of the working class. The socialists argued that addictions, as a social phenomenon, are the product of the conditions generated by capitalist exploitation, and therefore cannot be combated with punishment, but must be treated, on the one hand, through social reforms, and on the another, like any other disease, with medical treatment. At the same time, they argued that one of the main sources of the abuse of drink among the working masses was the despair and indifferentism resulting from it, and that the fight against addictions could only be waged by inspiring the workers with a cause to fight for. , that is, with a higher ideal of life like the one offered by socialism.